FEMINIST DISCOURSE AND LINGUOCULTURE: A THEORETICAL AND PRACTICAL ANALYSIS OF THE EVOLUTION OF THE FEMALE IMAGE (Web of Teachers: Inderscience Research, 2026)
This article explores the interrelation between feminist discourse and linguoculture, analyzing the evolution of the female image from both theoretical and practical perspectives. The study examines representations, stereotypes, and their linguistic manifestations across different historical periods and cultures. Special attention is given to the transformation of the female image within feminist frameworks, its social status, and the mechanisms of its reflection in language. The findings contribute significantly to the fields of linguocultural studies and gender research, offering both theoretical insights and practical implications.